2006
DOI: 10.1038/sj.ejcn.1602412
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D insufficiency in older female community-dwelling acute hospital admissions and the response to supplementation

Abstract: Objectives: A significant proportion of the older population may exhibit vitamin D insufficiency. We sought to establish the proportion of 25-hydroxyvitamin D (25OHD) insufficient individuals in an older female cohort presenting for acute medical admission and how they responded to supplementation. Design: A prospective cohort study. Setting: Hospital admissions followed up as a population-based study. Subjects: A total of 114 consecutive female acute medical admissions aged over 65 years from November 2003 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
10
0
2

Year Published

2007
2007
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 41 publications
5
10
0
2
Order By: Relevance
“…On the other hand, those with higher baseline levels are more likely to convert. The observation of highest absolute improvement in serum 25(OH)D in those with lowest baseline levels is also corroborated by previous research conducted in different patient populations including elderly, premenopausal and healthy individuals which found that participants with lower baseline serum 25(OH)D concentrations had a stronger serum 25(OH)D response to supplementation [40][41][42][43][44]. It has been hypothesized that hydroxylation of vitamin D3 to 25(OH)D is likely a saturable process, causing an attenuated response to supplementation in individuals with higher baseline serum 25(OH)D concentrations [45].…”
Section: Discussionsupporting
confidence: 70%
“…On the other hand, those with higher baseline levels are more likely to convert. The observation of highest absolute improvement in serum 25(OH)D in those with lowest baseline levels is also corroborated by previous research conducted in different patient populations including elderly, premenopausal and healthy individuals which found that participants with lower baseline serum 25(OH)D concentrations had a stronger serum 25(OH)D response to supplementation [40][41][42][43][44]. It has been hypothesized that hydroxylation of vitamin D3 to 25(OH)D is likely a saturable process, causing an attenuated response to supplementation in individuals with higher baseline serum 25(OH)D concentrations [45].…”
Section: Discussionsupporting
confidence: 70%
“…A indução enzimática pelas DAC fenitoína, carbamazepina e fenobarbital reduz os níveis séricos de vitamina D, e essa redução está associada à indução, pelas DAC, do receptor nuclear órfão do pregnane X, que possui 60% de homologia dos domínios de ligação do DNA com o receptor de vitamina D. A maior ativação do receptor do pregnane X é responsável por induzir a enzima do citocromo P 450 (CYP24), que metaboliza a 25(OH)D em ácido calcitroico, inativando-a 7,15,16 .…”
Section: Discussionunclassified
“…O presente trabalho demonstrou redução mais proeminente dos níveis séricos de vitamina D em pacientes do sexo feminino, assim como relatado por DeLappe et al, indicando que as mulheres na pós-menopausa passam a formar um grupo de risco para hipovitaminose D e devem ser especialmente acompanhadas quando em uso de DAC 15 . Gennari et al encontraram que a de ciência de estrógeno leva a menores índices de 25(OH) VITD seguidos de menor absorção intestinal de cálcio, favorecendo um quadro de hiperparatireoidismo secundário 16 .…”
Section: Discussionunclassified
“…The methods used for analysing the blood results were the same as that used in the previous study by DeLappe et al [10]. The laboratory in University Hospital Galway participates in UK external Quality Assessment Schemes for all parameters measured.…”
Section: Methodsmentioning
confidence: 99%
“…However, routine oral supplementation at commonly prescribed doses does not result in sufficient repletion of 25OH vitamin D levels in older, community dwelling, female acute hospital admissions [10]. The aim of this study is to establish if vitamin D intramuscular administration results in normalisation of 25OH vitamin D levels in this population.…”
Section: Introductionmentioning
confidence: 99%